A Randomized, Double‐Blinded, Phase II Trial of Gemcitabine and Nab‐Paclitaxel Plus Apatorsen or Placebo in Patients with Metastatic Pancreatic Cancer: The RAINIER Trial. (4th December 2017) - Ko, Andrew H.; Murphy, Patrick B.; Peyton, James D.; Shipley, Dianna L.; Al‐Hazzouri, Ahmed; Rodriguez, Francisco A.; Womack, Mark S.; Xiong, Henry Q.; Waterhouse, David M.; Tempero, Margaret A.; Guo, Shuangli; Lane, Cassie M.; et al.
Abstract: Lessons Learned : The addition of the heat shock protein 27 (Hsp27)‐targeting antisense oligonucleotide, apatorsen, to a standard first‐line chemotherapy regimen did not result in improved survival in unselected patients with metastatic pancreatic cancer. Findings from this trial hint at the possible prognostic and predictive value of serum Hsp27 that may warrant further investigation. Background: This randomized, double‐blinded, phase II trial evaluated the efficacy of gemcitabine/nab‐paclitaxel plus either apatorsen, an antisense oligonucleotide targeting heat shock protein 27 (Hsp27) mRNA, or placebo in patients with metastatic pancreatic cancer. Methods: Patients were randomized 1:1 to Arm A (gemcitabine/nab‐paclitaxel plus apatorsen) or Arm B (gemcitabine/nab‐paclitaxel plus placebo). Treatment was administered in 28‐day cycles, with restaging every 2 cycles, until progression or intolerable toxicity. Serum Hsp27 levels were analyzed at baseline and on treatment. The primary endpoint was overall survival (OS). Results: One hundred thirty‐two patients were enrolled, 66 per arm. Cytopenias and fatigue were the most frequent grade 3/4 treatment‐related adverse events for both arms. Median progression‐free survival (PFS) and OS were 2.7 and 5.3 months, respectively, for arm A, and 3.8 and 6.9 months, respectively, for arm B. Objective response rate was 18% for both arms. Patients with high serum level of Hsp27 represented a poor‐prognosis subgroup who may have derived modest benefit from addition of apatorsen. Conclusion: Addition of apatorsen to chemotherapy does not improve outcomes in unselected patients with metastatic pancreatic cancer in the first‐line setting, although a trend toward prolonged PFS and OS in patients with high baseline serum Hsp27 suggests this therapy may warrant further evaluation in this subgroup.